Gerakan Anti-Kolonialisme Menuju Indonesia Merdeka Dalam Perspektif Smelserian - Yudhi Rachman (Universitas Trunojoyo Madura, 2018)
This paper aims to provide an overview of Indonesia's social, political and economic conditions at the beginning of the 20th century. Changes in the movement of history are marked by the emergence of political resistance and revolutionary movements, including the establishment of the Islamic nationalist movement represented by the Sarekat Islam, the radical nationalist movement represented by Indische Partij and Insulinde, and the Marxist Communist Party of the Dutch East Indies. This study uses a library study method to explain the constellation of the movement of anti-colonialism in the Smelserian perspective. This research shows that social movements in Indonesia at the beginning of the 20th century arose due to dissatisfaction with existing social structures. Indisce Partij, for example, dared to declare itself a political party for all ethnic groups in Indonesia and collaborated with Sarikat Islam which was a large Islamic organization at that time. Likewise with the emergence of the communist movement which was initially brought in by a handful of Dutch people, it began to dare to voice its demands more radically in opposing Dutch imperialism and capitalism in Indonesia. This is the embryos of political resistance which color the constellation of the history of the Indonesian people towards their ideals of independence.